Safety and Effectiveness of Prolonged Magnesium Sulfate (MgSO4) Infusion for Asthma Exacerbation in Children - Awlad Thani, Saif Sulaiman; Alkhan, Atheer Ahmed; Al-Farsi, Muzna Yahya; Al Kamzari, Ahmed Mohammed (Journal of Pediatric Intensive Care, 2022)
The objective of this study was to assess the safety and describe treatment details of prolonged magnesium sulfate (MgSO4) infusion for children with asthma exacerbation. A retrospective cross-sectional study included children under 13 years of age who were admitted with asthma exacerbation and received at least 24 hours of MgSO4 infusion. One hundred children were included. No patients developed serious adverse events. The mean infusion duration was 74.2 hours. Eighty-nine percent recovered with no other bronchodilator infusions, and 94% did not require respiratory support escalation. Prolonged MgSO4 infusion is safe at a maximum dose of 30 mg/kg/h and may be beneficial for children with asthma exacerbation.
Keywords: magnesium sulfate infusion; asthma exacerbation; safety